2010
DOI: 10.1111/j.1439-0531.2008.01208.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol, Methyl-Formamide and Dimethyl-Formamide in Canine Semen Cryopreservation

Abstract: ContentsThe aim of the present work was to compare the efficiency of methyl-formamide (MF), dimethyl-formamide (DF) and glycerol (GL) as cryoprotectants in canine semen cryopreservation. For the experiment, pooled semen was submitted to one of the three cryoprotectants, with a final concentration of 3% in egg yolk-TRIS extender. Semen was subjectively evaluated for total and progressive motility, vigour and morphology. Sperm membrane functional integrity was assessed by hypo-osmotic swelling test (HOST), and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 43 publications
4
25
1
6
Order By: Relevance
“…These results are supported by the findings of Futino et al (2010) who reported that lecithin may have played a protective role during cryopreservation due to its low viscosity, lower presence of debris, improves the kinematics of sperm cells and rearrangements structure of the plasma membrane. The reduction in motility parameters in extenders containing higher (1.5% SL and 2 % SL) levels of lecithin compared to 1% SL may be related to high viscosity (Van Wagtendonk-de Leeuw et al, 2000).…”
Section: Resultssupporting
confidence: 84%
“…These results are supported by the findings of Futino et al (2010) who reported that lecithin may have played a protective role during cryopreservation due to its low viscosity, lower presence of debris, improves the kinematics of sperm cells and rearrangements structure of the plasma membrane. The reduction in motility parameters in extenders containing higher (1.5% SL and 2 % SL) levels of lecithin compared to 1% SL may be related to high viscosity (Van Wagtendonk-de Leeuw et al, 2000).…”
Section: Resultssupporting
confidence: 84%
“…Contraceptive effects of glycerol in mares has also been published (Demick et al 1976). There are a number of works dealing with the search for alternative cryoprotectants not only for stallion ejaculate, but also for the cryopreservation of sperm in other animal species and humans (Futino et al 2010;Swelum et al 2011). Investigated substances are specifically compounds of glycol: ethylene glycol, propylene glycol, diethylene glycol, dimethyl sulphoxide (Chenier et al 1998;Moore et al 2006;Hoffmann et al 2010) or various amides: formamide, methylformamide, dimethylformamide, acetamide or methylacetamide (Gomes et al 2002;Vidament et al 2002;Squires et al 2004;Alvarenga et al 2005;Ferreira et al 2008).…”
mentioning
confidence: 99%
“…In dogs, there is a shortage of studies regarding the periods used for cooling to 5 C [22, 23]. To minimize the cold shock process, the majority of the protocols for dog semen cryopreservation include long cooling periods from 23 C to 5 C. The most frequently employed period is from 60 to 120 min, corresponding to approximate mean cooling rates within the range of 0.15–0.3 C/min [5, 13,14,15,16, 24]. Our results clearly demonstrated that the use of rapid cooling at a rate of 2.25 C/min prior to freezing provides the same post-thaw sperm quality, in terms of motility and viability, as the values obtained with the use of a control rate of 0.2 C/min.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, during cryopreservation, spermatozoa are very sensitive to the rapid reduction from room temperature to 5 C [7]. Although dog spermatozoa are considered relatively resistant to cooling at 5 C [9], slow cooling rates prior to freezing are generally used for this species [5, 10,11,12,13]. For this reason, our hypothesis was that a rapid cooling rate prior freezing could be used efficiently for dog semen cryopreservation.…”
mentioning
confidence: 99%